TOKSISITAS EKSTRAK METANOL DAUN API-API (Avicennia marina (Forsk.) Vierh) TERHADAP RAYAP TANAH (Coptotermes curvignathus Holmgren) - Sulastri, .; Indrayani, Yuliati; Sisillia, Lolyta (Universitas Tanjungpura, 2018)
This study aims to examine the toxicity of A. marina leaf extracts to subterranean termite C. curvignathus and to determine the optimal concentration of A. marina leaf extract in inhibiting termite attack. A. marina leaf powder was extracted using methanol solvent for 48 hours, then the extract solution was evaporated using rotary evaporator for 1 hour to obtain extract in gel condition. Then whatman paper immer in extract solution at each concentration of 0%, 1%, 2%, 3%, 4% and 5% for 1 hour. Testing was done for 21 days. The parameters observed were termite mortality and weight loss of whatman paper. The highest mortality was found at concentrations of 5% with mortality of termite reach 100% with the weight loss of 0,857%. Concentration of 2% was noted as the optimal result with termite mortality value of 86,66% and weight loss of whatman paper reach 34,0725% wiht the level of anti-termite activity classified as B (strong).Â Keyword : Api-api leaf, Coptotermes curvignathus, extract, toxicity